Equivalent rate thresholds and financing risk in Indonesian Islamic commercial banks: Evidence from a nonlinear panel analysis - Rakhmat, Adrianna Syariefur; Effendi, Jaenal; Achsani, Noer Azam; Sahara, Sahara (Universitas Islam Indonesia, 2026)
IntroductionIndonesian Islamic banking has expanded considerably over the past two decades, yet its financing risk has not consistently remained lower than that of conventional banking. Islamic banks also continue to operate within a dual banking system in which conventional interest rates influence the pricing of Islamic financing. These conditions highlight the need to understand whether the equivalent rate of profit-and-loss-sharing financing affects Islamic banking risk in a linear or nonlinear manner.ObjectivesThis study examines the threshold effect of the equivalent rate of profit-and-loss-sharing financing on Indonesian Islamic banking risk. It also estimates a critical equivalent-rate level that may serve as an early warning indicator for financing risk mitigation.MethodThe study employed a quantitative explanatory design using quarterly unbalanced panel data from 15 Indonesian Islamic commercial banks between 2014 and 2024. Islamic banking risk was measured by the ratio of non-performing financing to total financing. The equivalent rate was calculated from returns on profit-and-loss-sharing financing relative to total profit-and-loss-sharing financing. The analysis applied a fixed-effects panel regression model with a least-squares dummy-variable estimator and corrected standard errors. Conventional interest rates, inflation, economic growth, the exchange rate, and the coronavirus disease 2019 period were included as control variables.ResultsThe equivalent rate of profit-and-loss-sharing financing demonstrated a significant inverted U-shaped relationship with Islamic banking risk. Below the estimated threshold of 10.96 percent, an increase in the equivalent rate raised non-performing financing because higher financing costs increased customers’ repayment burdens. Above the threshold, however, a higher equivalent rate reduced financing risk, indicating that Islamic banks strengthened customer screening, feasibility assessment, and project monitoring when expected financing returns were sufficiently high. Conventional interest rates showed a U-shaped relationship with Islamic banking risk, with an estimated threshold of 6.01 percent. Inflation significantly reduced financing risk, whereas economic growth, exchange rates, and the coronavirus disease 2019 period had no significant effects.ImplicationsThe findings support the use of the equivalent-rate threshold as an early warning mechanism. Islamic banks should improve financing portfolio diversification, strengthen customer selection, monitor financed projects continuously, and design profit-and-loss-sharing products that generate stable returns without increasing default risk.Originality/NoveltyThis study contributes new evidence on the nonlinear relationship between equivalent rates and Islamic banking risk and provides a measurable threshold for risk management in Indonesian Islamic commercial banks.